Thromboembolism in Older Adults - Gross, Peter L.; Chan, Noel C. (Frontiers in Medicine, 2021)
Arterial and venous thromboembolism are both more common in older adults. The use of anticoagulants, the mainstay to prevent thromboembolism, requires consideration of the balance between risk and benefit. Such consideration is even more important in the very elderly in whom the risk of anticoagulant-related bleeding and thrombosis are higher. This review will focus on the challenges of implementing and managing anticoagulant therapy in older patients in an era when the options for anticoagulants include not only vitamin K antagonists (VKAs), but also direct-acting oral anticoagulants (DOACs).